PENGEMBANGAN ALAT PERAGA PADA MATERI ENERGI LISTRIK DI SD NEGERI 11 DANAU KANDUNG SULI - Suganda, Tomy; S, Stepanus Sahala; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe use of visual aids as the media in learning is choosed because of its efficiency and multitasking potential that can be used for the learning activities. The purpose of this research is to identify and develop the visual aid in order to improve the students? learning outcomes, about the energy of electricity in Science subject of 11 Danau Kadung Suli Elementary School . This development research uses Borg & Gall Research and Development approach (1983:772). The subjects in this research are the 14 fourth grader students of 11 Danau Kandung Suli in the school year of 2018/ 2019, Jongkong District, Kapuas Hulu Regency. As for the data gathering in this research are: (1) Interview; (2) Observation; (3) Documentary Study; (4) Test; and (5) Validation. The data analysis in this research consists of qualitative analysis and T-Test. The result of this research shows that the Danau Kandang Suli (DKS) Solar Ship visual aid that has been developed is effective to improve students? learning outcomes. To get that result, the datas were being analyzed to know, how big its effect to improve students? learning outcomes. The result of pretest and posttest shows that the effect of the visual aid has the signification of= 0,00 < ? 0,05, which means there is difference of students? learning outcomes before and after learning process using visual aid that has been developed. The impact in using visual aid is categorized as high that is ES > 0,8 , and the gained ES score of the used visual aid was 1,47.Keyword: Development, Eenergy of electicity, Visual aid.